2017
DOI: 10.1088/1361-6528/aa8791
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite-loaded nanoparticles inhibit the invasion and metastasis of a hepatocellular carcinoma:in vitroandin vivostudy

Abstract: Postoperative recurrence and metastasis are the major problems for the current treatment of hepatocellular carcinomas (HCC) in the clinic, including hepatectomy and liver transplantation. Here, we report that arsentic-loaded nanoparticles (ALNPs) are able to reduce the invasion of HCC cells in vitro, and, more importantly, can strongly suppress the invasion and metastasis of HCC in vivo without adverse side effects. Compared to free drug arsenic trioxide , ALNPs can deliver the drug into cancer cells more effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Controlling the release of NPs helps to overcome or reduce the multidrug resistance of HCC cells. 38 This is very important for the preparation of anti-cancer NPs and is essential for the treatment of HCC diseases. Stability The test results show that BA-C 60 (OH) n -GBP-TPGS-NPs can keep stable performance for 30 days or 24 hours in the simulated medium.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling the release of NPs helps to overcome or reduce the multidrug resistance of HCC cells. 38 This is very important for the preparation of anti-cancer NPs and is essential for the treatment of HCC diseases. Stability The test results show that BA-C 60 (OH) n -GBP-TPGS-NPs can keep stable performance for 30 days or 24 hours in the simulated medium.…”
Section: Discussionmentioning
confidence: 99%
“…95 In another work, HSNs loaded with ATO in the presence of Mn(II) ions were examined in the treatment of HCC. 72 It was shown that the ATO-NPs could decrease the invasion of HCC cells not only in vitro but also in vivo without adverse side effects (determined by pathology tests of the main organ tissues). Zhao et al demonstrated that HSNs containing manganese arsenite complexes could be used as a pH-sensitive multifunctional DDS capable of real-time monitoring of ATO release by activatable T 1 imaging in MRI (Figure 5).…”
Section: Hollow Silica Nanoparticlesmentioning
confidence: 99%
“…[67][68][69][70] To increase the ATO loading even more, the second approach was applied to hollow MSNs (Figure 4C). [71][72][73] Thiol group and amino group functionalized MSNs Silica nanoparticles functionalized with thiol groups were used to bind ATO to develop nano drug for treating MDA-MB-231 triple-negative breast cancer (TNBC). 63 The inner and outer surfaces of MSNs were functionalized with thiol groups not only for the ATO binding, but also to conjugate targeting agents to the outer surface.…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…[34,35] In detail, nanoparticles carrying drugs or nanoparticle-based immunotherapy has been reported, both of which have anti-metastasis effects for tumor therapy. [36][37][38] Additionally, a new method combining PTT and advanced imaging techniques has also been developed as a potential choice for anti-metastasis therapy, and the mechanism involves hyperthermia to burn lymph nodes that have been invaded by cancer cells. [39] However, among the nanoparticle applications in these antimetastatic strategies, nanoparticles are more commonly used as vehicles or in indirect steps.…”
Section: Introductionmentioning
confidence: 99%